Peran Belanja Pemerintah dan Pajak terhadap Pertumbuhan Ekonomi Kabupaten dan Kota di Sumatera - Roosemarina Anggraini Rambe; Ratu Eva Febriani (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
Sumatra is the driving force for the economy in Indonesia after Java. Compared to 4 other regions in Indonesia, apart from Java, the average economic growth in Sumatra is more stable. However, the contribution of GRDP of districts and cities in Sumatra to Indonesia has decreased, which indicates that the economic strength of Sumatra is declining. This study aims to analyze the effect of government spending, local taxes, and regional spliting on the economic growth of districts and cities in Sumatra. This study uses secondary data obtained from BPS and the Ministry of Finance of the Republic of Indonesia in the form of panel data, with 154 districts and cities in Sumatra during 2011-2016. The analysis method used is panel data regression. The results showed that the best regression model produced was the Fixed Effect Model. With the fixed effect model, it is found that government spending and local taxes have a significant positive effect on the economic growth of districts and cities in Sumatra. Meanwhile, for the regional split status variable, it is known that the blooming districts and cities have lower economic growth. The results of this research imply that local governments should allocate expenditure properly and strive for more optimal district/city tax collection through tax extensification so that the district and city economies can grow higher. On the other hand, the government is expected to evaluate the division of districts and cities because regional expansion did not promote economic growth during the research period.